The Expansion of European Bureaucracy - Ioan Popescu (CES Working Papers, 2011)
Throughout history political building meant also the development of the administration. Descriptions and complaints about bureaucracy in the EU are numerous, but the supra-national bureaucracy is not exactly replicating the national one. Firstly because the European organizations enjoy powers and privileges that no national bureaucracies have, and secondly, it is far too small to directly manage 500 million people.
Keywords: H21; K29; 330; bureaucracy; European Union; agencies Romania